Technology Blueprint : Sunbrella Enterprise / Nurshamimi Mohd Kamis - Mohd Kamis, Nurshamimi (2020)
Sunbrella Enteprise is a company which distribute a very handful, useful and affordable product. It produces an easy-to-use umbrella names as Sunbrella which helps life to get easier and more comfortable. The goal of this product is to make the world wide population able to stay dry with a new and innovative umbrella that always keep you feeling cool. With such a product being put on the market, it will give us a chance to take consumers away from the competition in the umbrella industry